TROIKA INTERPROFESSIONAL (TIP) GERONTOLOGICAL EDUCATION MODEL: THE POWER OF THREE IN PRIMARY CARE. (11th November 2018) - Harrington, C; Stokes, K; Hardin, S; Steinweg, K; Pabbu, B; Duffrin, C; Nye, A
Abstract: Team-based learning models for primary care are critical to achieving optimal outcomes for elders in rural communities. The Troika InterProfessional (TIP) Gerontology Education Model describes the outcome model for a student team of three primary care professions who learn and apply gerontology knowledge in a virtual clinic environment. Representative students from Medical 3rd year clerkship, physician assistant, family, and adult-gerontology primary care nurse practitioner programs rotate through a faculty-facilitated Virtual Clinic Round Table case study discussion. Virtual patients present in the clinic with a variety of complex health issues. The student team is charged to use principles of interprofessional education and consensus building to care for the patient according to best practices. Principles of logical prescribing, potentially inappropriate medications, psychotropic medication management, pain management, health promotion, and disease prevention were included to simulate the complexity of older adults in the rural health care setting. Patient care score (R= 84–97/100). One way ANOVA between-group difference was found for M3 and FNP students for Attitudes Toward Interprofessional Education Survey: (α=.875); F(10, 257) = 3. 674 (p=.000), Students reported value working together and perceived differences in philosophies and models of care result in similar outcomes. One participant reported, "The different perspectives were both very educational as well as humbling. It showed the many benefits of working as a team". Interprofessional primary care education opportunities are vital to promoting collaborative care in practice. The positive results and feedback resulted in all programs embedding this IPE activity into their respective geriatric curricula.